Neferine Ameliorates Sepsis-Induced Myocardial Dysfunction Through Anti-Apoptotic and Antioxidative Effects by Regulating the PI3K/AKT/mTOR Signaling Pathway - Qi, Zhen; Wang, Renrong; Liao, Rongheng; Xue, Song; Wang, Yongyi (Frontiers in Pharmacology, 2021)
Septic cardiomyopathy is a common complication of severe sepsis, which is one of the leading causes of death in intensive care units. Therefore, finding an effective therapy target is urgent. Neferine is an alkaloid extracted from the green embryos of mature seeds of Nelumbo nucifera Gaertn which has been reported to possess various biological activities and pharmacological properties. This study aims to explore the protective effects of neferine on LPS-induced myocardial dysfunction and its mechanism. The LPS-induced cardiac dysfunction mouse model was employed to investigate the protective effects of neferine. In this study, we unveiled that neferine administrated remarkably improved the cardiac function and survival rate and ameliorated the damage of morphology in heart tissue of LPS-induced mice. Neferine also improved cell viability and mitochondrial function and reduced cell apoptosis and production of reactive oxygen species (ROS) in LPS-treated H9c2 cells. In addition, neferine significantly upregulated Bcl-2 expression and suppressed Cleaved-caspase 3 activity in heart tissues and H9c2 cells induced by LPS. Meanwhile, we found that neferine also upregulated PI3K/AKT/mTOR signaling pathway in LPS-induced H9c2 cells. Conversely, LY294002 (a PI3K inhibitor) reversed the protective effect of the neferine in LPS-induced H9c2 cells. Therefore, we conclude that neferine ameliorates LPS-induced cardiac dysfunction by activating PI3K/AKT/mTOR signaling pathway and might be a promising therapeutic strategy for the treatment of LPS-induced cardiac dysfunction.